Failed Surgery in Primary Hyperparathyroidism – What has Changed with Time - Wirowski, D.; Goretzki, P. E.; Schwarz, K.; Lammers, B. J.; Dotzenrath, C.; Röher, H.-D. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Advanced preoperative imaging of parathyroid adenomas and intraoperative parathyroid hormone determination optimized the results in the surgical treatment of primary hyperparathyroidism patients. We asked, whether reasons for failure have changed during the last 25 years.We retrospectively analyzed operations for persistent primary hyperparathyroidism in our department between 2001 and 2011 (n=67), and compared these results to our experience between 1986 and 2001 (n=80).From 2001 to 2011, 765 primary hyperparathyroidism patients were operated on at our department. All but 4 patients were cured (761/765, 99.5%). 67 operations were performed for persistent primary hyperparathyroidism. Main reasons for failure were a misdiagnosed sporadic multiple gland disease in our own patients (18/29, 62.1%), and an undetected solitary adenoma in patients referred to us after initial operation in another hospital (22/38, 57.9%) (statistically significant). From 1986 to 2001 (1 105 primary hyperparathyroidism patients), main indications for re-operation due to persistent disease were an undiagnosed sporadic multiple gland disease in our own patients (15/24, 62.5%), and a missed solitary adenoma in patients being operated on primarily somewhere else (38/56, 67.9%) (statistically significant).Comparing our experience in 147 patients with persistent primary hyperparathyroidism being operated on between 2001–2011 and 1986–2001, not much has changed with the modern armamentarium of improved preoperative imaging or intraoperative biochemical control. Whereas sporadic multiple gland disease was the most common reason for unsuccessful surgery in experienced hands, other units mainly failed due to an undetected solitary adenoma. Re-operations for persistent primary hyperparathyroidism performed by us were successful in 93.8% (2001–2011) and 96.0% (1986–2001), respectively.
Keywords: primary hyperparathyroidism; persistent hyperparathyroidism; recurrent hyperparathyroidism; hereditary hyperparathyroidism; ectopic parathyroid glands; multiple gland disease